Pengaruh Implementasi Aplikasi Keuangan Berbasis Digital Terhadap Optimalisasi Kinerja UMKM Di Kecamatan Medan Johor - Izzati, Nadhila; Kurnia Ningsih, Heny Tri Astuti; Khairani Lubis, Farida (VALUE, 2025)
This study aims to investigate the impact of digital financial application usage on the performance of micro, small, and medium enterprises (MSMEs) in the Medan Johor District. A quantitative research design was adopted, utilizing a survey as the primary data collection method. Data were gathered using purposive sampling by distributing questionnaires to MSME operators who utilize the "Buku Warung" app. Findings from simple linear regression analysis reveal that employing digital financial tools significantly enhances MSME performance. This improvement is reflected in more organized, precise, and efficient financial management, enabling MSME operators to better track transactions, oversee cash flow, and make informed business decisions. Nonetheless, the study identified challenges such as limited technological literacy among MSME operators and inadequate internet access, which may impede optimal application use. Furthermore, entrenched habits and insufficient training contribute to some business owners' reluctance to transition from traditional methods. Consequently, efforts to boost digital literacy, increase awareness, and strengthen governmental infrastructure support are essential to promote wider adoption of digital financial technologies. The research is expected to contribute to the sustainable and effective development of MSMEs through the strategic use of digital technology.